Pedagogic Competence of PAUD Teachers in Conducting Disaster Mitigation - Mulyani, Dewi; Nur Inten, Dinar; Neneng Permatasari, Andalusia; Aziz, Helmi (KnE Social Sciences, 2023)
The occurrence of disasters often brings suffering to those who are affected. Early childhood (AUD: Anak Usia Dini) belongs to the category of vulnerable groups to become victims. So they need the protection and assistance of caring adults before and during a disaster. PAUD (Pendidikan Anak Usia Dini or Early Childhood Education) teachers are adults who are close to early childhood, in addition to parents and caregivers. PAUD teachers have a great possibility to provide protection and assistance both before and after the disaster. One of the ways to do this is through disaster mitigation education. However, to provide assistance and protection, PAUD teachers need understanding and skills in disaster mitigation lessons. Keywords: PAUD teachers, disaster mitigation, PAUD students